The Relationship Between the Dark Triad and Internet Adaptation Among Adolescents in China: Internet Use Preference as a Mediator - Jin, Can Can; Wang, Bo Chen; Ji, Ai Tong (Frontiers in Psychology, 2019)
This study aims to examine the relationship among the Dark Triad personality traits, Internet use preferences and Internet adaptation. In all, 1934 middle school students (aged 11-22) from Beijing and Kunming in China completed a self-reported questionnaire that measured the Dark Triad, Internet use preferences (information communication, recreation, information acquisition and online transaction) and Internet adaptation (positive/negative Internet adaptation). Correlations revealed that there were significant correlations among the Dark Triad, Internet use preferences and Internet adaptation. Multiple regression analysis indicated that psychopathy predicted Internet adaptation more significantly than Machiavellianism or narcissism. Information acquisition positively predicted positive Internet adaptation and negatively predicted negative Internet adaptation, and recreation and online transaction were just the opposite. The SEM results suggested that Internet use preferences partially mediated the relationship between the Dark Triad and Internet adaptation. We discussed the importance of the combined effect of the Dark Triad and Internet use preferences on Internet adaptation.